UJI KUALITATIF KANDUNGAN HARA KOMPOS CAMPURAN BEBERAPA KOTORAN TERNAK PELIHARAAN - Tumimbang, Meity; Tamod, Zetly E.; Kumolontang, Wiesje (Universitas Sam Ratulangi, 2016)
ABSTRACT Â The purpose of this research is to find out the nutrient content on five types of livestock manure compost which made of the mix of some livestock manure. This research uses three stages starting from the inventory, then analyzing the data, and finally interpretation of the data for the parameters: follow-up material, color, odor, moisture or water content, Reaction Fertilizer PH, Levels of C Organic, Levels of Total N, Total P, Total K, and Fe. The inventory stage is conducted in laboratory using fast accurate qualitative methods based on Soil Research Center manual guide (2015). The research showed the results of the analysis of physical quality of blackish brown color, soil smells, moisture content less than 50% have met the Indonesian National Standard (SNI) 19-7030-2004. However, based on Decree of the Minister of Agriculture no 28/Permentan/SR.130/B/2009, the water content obtained under the requirements is only in the range of 7.82 to 13.31 from 15-25% while the follow-up material showed <2%. The test results using a set of compost test tools showed N Total content of the livestock manure mixture compost that were made in the range of 2-3% (SNI standard >0,4% and Decree of the Minister of Agriculture <6%), P2O5 1-1.5% (SNI standard >0.1% and Decree of the Minister of Agriculture <6%), C-Organic 10% (SNI standard >9,8-32% and Decree of the Minister of Agriculture >12%), and Fe content 1000-2000 ppm (Decree of the Minister of Agriculture standard 0-8000 ppm), PH 5-7 (SNI standard 6,8 and Decree of the Minister of Agriculture standard 7,49). Key words: compost, domesticated cattle